2016
DOI: 10.1016/j.jpag.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Preservation after a Cancer Diagnosis: A Systematic Review of Adolescents', Parents', and Providers’ Perspectives, Experiences, and Preferences

Abstract: Study Objective Survival into adulthood is now a reality for many adolescents facing cancer. FP (Fertility Preservation) is a rapidly advancing field, but oncology providers and health systems struggle to incorporate the newest FP technologies into the clinical care of adolescents. Our objective was to systematically review and synthesize the available data regarding the perspectives, experiences, and preferences of adolescents, parents, and oncology providers about FP to inform clinical implementation of FP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 55 publications
(40 reference statements)
1
41
0
1
Order By: Relevance
“…suggest the influence of a developmental perspective on adolescent decision making . A systematic review of FP perspectives among patients, parents, and providers supports this hypothesis . Across several studies, AYA survivors increasingly value future parenthood and reported regret about prior decisions or limited options for FP.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…suggest the influence of a developmental perspective on adolescent decision making . A systematic review of FP perspectives among patients, parents, and providers supports this hypothesis . Across several studies, AYA survivors increasingly value future parenthood and reported regret about prior decisions or limited options for FP.…”
mentioning
confidence: 95%
“…Literature on parenting desires among childless adults in the general population has found that age and relationship formation are significant factors in the timing of childbearing goal‐adjustment . Although young male patients and survivors may not presently prioritize fatherhood, throughout the literature, adolescents cited a desire to keep options open as a factor in pursuing FP …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Uit een systematische review van internationale studies met oncologische patiënten bleek dat, ten tijde van de kankerdiagnose, in wisselende mate (30-87 % van de gevallen) counseling plaatsvindt over fertiliteit, effecten van de therapie op fertiliteit en fertiliteitspreservatie [6]. In de dagelijkse praktijk is het bespreken van fertiliteit niet de eerste prioriteit tijdens een slechtnieuwsgesprek over een kankerdiagnose.…”
Section: Introductieunclassified